2020
DOI: 10.1371/journal.pone.0234328
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between single nucleotide polymorphisms in FABP4 and meat quality and lipid metabolism gene expression in Yanbian yellow cattle

Abstract: FABP4 is a candidate gene for carcass and meat quality traits in livestock and poultry. However, the effects of FABP4 have not been examined in the Yanbian yellow cattle, an economically important local cattle breed in China. In this study, we characterized single nucleotide polymorphisms (SNPs) in FABP4 in this cattle breed and their associations with meat quality traits. Six SNPs (referred to as SNP1-6) were identified in FABP4 by direct sequencing and polymerase chain reaction-restriction fragment length po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
8
1
Order By: Relevance
“…We found that FABP4 was a downregulated DEM, which not only regulated the differentiation of bovine adipocytes in the PPAR signaling pathway and supported the transport of extracellular FAs but was also involved in lipolysis and FA transport in different tissues ( 71 , 72 ). A recent study on the FABP4 gene of Yanbian cattle showed that a SNP in FABP4 substantially affected the fat content, protein content, and marbling level ( 73 ). Li et al ( 74 ) found that with increasing age, the concentration of SFA in Yanbian cattle decreased, and the concentration of MUFA increased proportionally with an increase in the percentage of intramuscular lipids leading, in turn, to an increase in the expression of the FABP4 gene.…”
Section: Discussionmentioning
confidence: 99%
“…We found that FABP4 was a downregulated DEM, which not only regulated the differentiation of bovine adipocytes in the PPAR signaling pathway and supported the transport of extracellular FAs but was also involved in lipolysis and FA transport in different tissues ( 71 , 72 ). A recent study on the FABP4 gene of Yanbian cattle showed that a SNP in FABP4 substantially affected the fat content, protein content, and marbling level ( 73 ). Li et al ( 74 ) found that with increasing age, the concentration of SFA in Yanbian cattle decreased, and the concentration of MUFA increased proportionally with an increase in the percentage of intramuscular lipids leading, in turn, to an increase in the expression of the FABP4 gene.…”
Section: Discussionmentioning
confidence: 99%
“…The fatty acid-binding protein-4 (FABP4) plays a role in the absorption, transport, and metabolism of long-chain fatty acids [ 66 , 67 , 68 ]. Previous studies reported an association between FABP4 polymorphism and carcass characteristics [ 35 ] and fat deposition [ 66 , 67 ]. In Japanese Black cattle, Hoashi et al [ 69 ], reported that genotype 174V of the FABP4 gene was significantly associated with 16:1 and 18:2.…”
Section: Discussionmentioning
confidence: 99%
“…SCD, FABP4, and FASN are lipogenic genes known to influence fat deposition and fatty acid metabolism in meat and adipose tissues [ 6 ]. SNP identification may further enhance our current understanding of the contribution of lipogenic genes to intramuscular fat deposition and fatty acid composition in the muscle tissue of diverse beef cattle breeds [ 35 , 36 , 37 , 38 , 39 ]. The identified SNP can be used effectively for marker-assisted selection to improve health-beneficial n-3 LC-PUFA and meat eating quality traits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FABP4 gene is an important protein for long-chain fatty acid transport in mammals, and its polymorphism is associated with growth, fat deposition, and carcass traits in cattle [66][67][68]. Substitution of the G to C allele of the g.44677587 (rs723716479) locus was positively correlated with CLA, previously inversely linked with the risk of colorectal and breast cancer in some population-based studies [69].…”
Section: Fatty Acid Binding Protein 4 Gene Polymorphismsmentioning
confidence: 99%